Transfer of radionuclides to plants of natural ecosystems at the Semipalatinsk Test Site. (June 2018) - Larionova, N.V.; Lukashenko, S.N.; Kabdyrakova, A.M.; Kunduzbayeva, A.Ye.; Panitskiy, A.V.; Ivanova, A.R.
Abstract: A systematic study devoted to 137 Cs, 90 Sr, 241 Am, 239+240 Pu radionuclides in vegetation cover from several spots of the Semipalatinsk test site (STS) is summarised in this paper, highlighting the main findings obtained. The analysed spots are characterized by various types of radioactive contamination. Transfer factors (Tf) required for the quantitative description of the radionuclides transition from the soil to aboveground plant parts were determined, being found that, on average, the minimum Tf for all the radionuclides concerned were determined on the "Experimental Field" ground, followed by the determined ones in the "plumes" of radioactive fallout and in the conditionally "background" territories analysed. The highest transfer factors were characteristic of zones of radioactive streamflows and places of warfare radioactive agent (WRA) tests. On the other hand, ordering the radionuclide transferring factors in descending order, the following sequence was obtained: 90 Sr Tf > Cs Tf > 239+240 Pu Tf > 241 Am Tf, with the 90 Sr Tf, on the average, exceeding the 137 Cs Tf by 8 times and exceeding the 239+240 Pu Tf by up 16 times. 239+240 Pu Tf values were up to 3 times higher than the 241 Am Tf. The exception to the indicated radionuclide Tf descending order corresponded to places of WRA tests where Tf of radionuclides of interest by plants follows the sequence 90 Sr > 239+240 Pu > 137 Cs. Highlights: Transfer factors have been determined for 90 Sr, 137 Cs, 239+240 Pu and 241 Am at several spots of the Semipalatinsk Test site. Differences in the Tfs determined have been found between various areas affected by different types of contamination. The Tfs obtained can be classified in the following descending order: 90 Sr Tf > 137 Cs Tf > 239+240 Pu Tf > 241 Am Tf. The determined STS transfer factors have been compared with the compiled ones in the IAEA worldwide database.